IDENTIFICATION OF SECOND PHASE DEPOSITED ON La-DOPED SrTiO3 PEROVSKITES SYNTHESIZED BY CITRIC-GEL METHOD - Moriga, T.; Liu, X.; Minakata, R.; Minato, R.; Nakata, K.; Murai, K.; Shih, S. J.; Mori, M. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
We examined deposition process of the second phase during sintering Sr0.7La0.3TiO3 perovskite at 1400°C and analyzed the detailed composition by means of SEM-EDX technique. The second phase deposited at the corners of the Sr0.7La0.3TiO3 matrix grains was confirmed to be Sr-doped rare-earth B-type La2O3.